EXPLORING THE IMPACT OF WORK MOTIVATION ON WORK READINESS: A QUANTITATIVE ANALYSIS AMONG MUTIARA BANDUNG VOCATIONAL SCHOOL STUDENTS - Kurniawan, Ichsan; Sukandar, Aan; Permana, Tatang (Journal of Mechanical Engineering Education (Jurnal Pendidikan Teknik Mesin), 2023)
The background of this research is that work readiness tends ti decrease due to several factors, one of which is work motivation. This study aims to determine the relationship between work motivation and work readiness in Mutiara Bandung Vocational School students. This research is a descriptive research and with a quantitative approach and survey design research type. Respondents in this study consisted of 40 students at SMK Mutiara Bandung who were or had implemented street vendors. The result of these findings indicate that work motivation has a strong and positive correlation with work readiness, and work motivation has a strong and positive relationship with a percentage of 42,6%. Based on these findings, the relationship beetwen work motivation and work readiness is in the strong, positive, and significant category.